Radial evolution of the solar wind in pure high-speed streams: HELIOS revised observations. Issue 3 (10th December 2018) - Perrone, Denise; Stansby, D; Horbury, T S; Matteini, L
Abstract: Spacecraft observations have shown that the proton temperature in the solar wind falls off with radial distance more slowly than expected for an adiabatic prediction. Usually, previous studies have been focused on the evolution of the solar-wind plasma by using the bulk speed as an order parameter to discriminate different regimes. In contrast, here, we study the radial evolution of pure and homogeneous fast streams (i.e. well-defined streams of coronal-hole plasma that maintain their identity during several solar rotations) by means of re-processed particle data, from the HELIOS satellites between 0.3 and 1 au. We have identified 16 intervals of unperturbed high-speed coronal-hole plasma, from three different sources and measured at different radial distances. The observations show that, for all three streams, (i) the proton density decreases as expected for a radially expanding plasma, unlike previous analysis that found a slower decrease; (ii) the magnetic field deviates from the Parker prediction, with the radial component decreasing more slowly and the tangential more quickly than expected; (iii) the double-adiabatic invariants are violated and an increase of entropy is observed; (iv) the collisional frequency is not constant, but decreases as the plasma travels away from the Sun. This work provides an insight into the heating problem in pure fast solar wind, fitting in the context of the next solar missions, and, especially for Parker Solar Probe, it enables us to predict the high-speed solar-wind environment much closer to the Sun.